Strategi Produk, Harga, Promosi, Dan Keamanan Terhadap Pengambilan Keputusan Masyarakat Dalam Memilih Blibli.Com Sebagai Pasar Online Di Jakarta - Lutfi Prajayanti (SMARTINDO, 2022)
Purpose of this article : The purpose of this article is to find out the influence of product strategy, price, promotion, and security in people’s decision which is choosing Blibli.com as online marketplace or e-commerce in Jakarta. Methodology: This study uses primary data and sample with the unit of analysis are people of Jakarta who shop at Blibli.com. Results: Variables of product strategy have a positive effect on people’s decision to choose Blibli.com as online marketplace or e-commerce.Keywords: Making decision, Online Marketplace, Price, product’s strategy, promotion, security,.